The Role of the Police in Creating Legal Effectiveness in Facing the Dynamics of the Indonesian Criminal System - Zarma Putra; Gunarto Gunarto (Jurnal Hukum Khaira Ummah, 2025)
Abstract. There is a need for a paradigm shift in the criminal justice system across all subsystems, including the police, as the primary entry point for criminalization, which is then pursued through criminal justice, or what is known as the gatekeepers of the criminal justice system. The police, whose role is crucial in addressing Indonesia's criminal justice system challenges, need a concrete response to the evaluation of various issues in criminal law enforcement and sentencing. The aims of this research are (1) the nature of the reality of the development of the Indonesian criminal justice system, (2) the role of the Police in realizing legal effectiveness in addressing the problems of Indonesian criminal justice, (3) a formulative concept for the Police in achieving legal effectiveness in the Indonesian criminal justice system. The approach method used in this research is normative juridical. The specifications of this research are analytical descriptive. The data source used is secondary data. Secondary data is data obtained from library research consisting of primary legal materials, secondary legal materials and tertiary legal materials. The research results and discussion can be concluded: (1) According to the provisions in Article 10 of the Criminal Code, the types of criminal sanctions are divided into several types, including the main penalty consisting of the death penalty, imprisonment, detention, and fines. Then the additional penalties consist of the revocation of certain rights, confiscation of certain items, and the announcement of the judge's decision. (2) The presence of Police Regulation No. 8 of 2021 concerning Restorative Justice provides space for Police members in the Criminal Investigation Unit to resolve cases more quickly and provides normative guidelines for acting to resolve criminal cases using the restorative justice method. In terms of handling cases as determined by Police Regulation No. 8 of 2021, it can be seen that when there is a criminal complaint report where the severity of the case is assessed to be categorized as a light criminal case, that is when restorative justice is attempted. (3) The agenda for legal reform in the process of resolving criminal cases with restorative justice is outlined in the formal source of criminal law, namely the Criminal Procedure Code, as an idea of legal legitimacy for the realization of the legality of the application of restorative justice, which will be more precise and will fulfill legal certainty if accompanied by adequate and comprehensive legal instruments.